Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acsomega.7b01029
|View full text |Cite
|
Sign up to set email alerts
|

Immunosensor for Pancreatic Cancer Based on Electrospun Nanofibers Coated with Carbon Nanotubes or Gold Nanoparticles

Abstract: We report the fabrication of immunosensors based on nanostructured mats of electrospun nanofibers of polyamide 6 and poly(allylamine hydrochloride) coated either with multiwalled carbon nanotubes (MWCNTs) or gold nanoparticles (AuNPs), whose three-dimensional structure was suitable for the immobilization of anti-CA19-9 antibodies to detect the pancreatic cancer biomarker CA19-9. Using impedance spectroscopy, the sensing platform was able to detect CA19-9 with a detection limit of 1.84 and 1.57 U mL–1 for the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 51 publications
(100 reference statements)
0
23
0
Order By: Relevance
“…They established that protease expression was significantly higher in pancreatic cancer lines compared to control groups. Their experiment revealed that cathepsin B, MMP-1 and MMP-2, arginase and urokinase plasminogen activators, detected through liquid biopsy, represent great biomarkers for the detection of PC, thus establishing an enzymatic signature for PC and also proving that nanoparticles can be of use in the early detection of this type of cancer [ 36 , 37 , 38 , 39 ].…”
Section: Fluorescence Nanobiosensors For Ultrasensitive (Sub-femtomolar) Arginase and Protease Identificationmentioning
confidence: 99%
“…They established that protease expression was significantly higher in pancreatic cancer lines compared to control groups. Their experiment revealed that cathepsin B, MMP-1 and MMP-2, arginase and urokinase plasminogen activators, detected through liquid biopsy, represent great biomarkers for the detection of PC, thus establishing an enzymatic signature for PC and also proving that nanoparticles can be of use in the early detection of this type of cancer [ 36 , 37 , 38 , 39 ].…”
Section: Fluorescence Nanobiosensors For Ultrasensitive (Sub-femtomolar) Arginase and Protease Identificationmentioning
confidence: 99%
“…Electrospun NFs in combination with CNTs have also been investigated as biosensors for the detection of early stages of pancreatic cancer by the use of the biomarker CA19-9. Electrospun NFs made of poly(allylamine hydrochloride) and polyamide 6 were covered with MWCNTs, and CA19-9 detection were determined by electrochemical impedance spectroscopy [79]. This biosensor showed a good sensitivity for the antigen without the rest of the blood components could suppose interference in the detection.…”
Section: Electrospun Nanofibers For Drug Delivery Applicationmentioning
confidence: 99%
“…In the same way as with electrospun NFs made of poly(allylamine hydrochloride) and polyamide 6 covered with MWCNTs, these NFs were also covered with gold nanoparticles for the detection of the pancreatic cancer biomarker CA19-9. In this case, lower biomarker detection thresholds were obtained with the use of gold nanoparticles (1.57 U mL −1 ) compared with the use of MWCNTs (1.84 U mL −1 ) [79].…”
Section: Electrospun Nanofibers For Drug Delivery Applicationmentioning
confidence: 99%
“…In addition to polymer nanofibers, the combination of MNPs and carbon nanofibers (CNFs) also attracts great interest [20,34]. Compared with other materials, the super-small size of nanoparticles not only gives them unique properties, but also makes them in an energy unstable state due to their huge specific surface area and surface energy [35].…”
Section: Electrospinning Np-based Materials Interfacesmentioning
confidence: 99%